Navigating Challenges Through Puberty in Islamic Boarding Schools for Girls: Students’ Knowledge and School Support - Thoifah, I'anatut; Asih, Ria; Colovos, Dimitra; Lukitasari, Mifetika (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
Managing puberty while away from families can be challenging for young adults, especially women. A pedagogical approach that combines reproductive health literacy with religious principles will equip students to face puberty responsibly and follow religious guidance. This study aims to explore the levels of female students’ knowledge in handling puberty and the relationship between these levels and the support the students receive from an Islamic boarding school. Two sets of questionnaires were distributed to female students (n=189) in a private Islamic Boarding School in Malang, Indonesia. The data was analysed using R version 4.4.0 with a Pearson’s product-moment correlation, completed with Spearman to measure the effect of students’ demography on their knowledge and school support. Results show that a moderately significant relationship was found between students’ knowledge and school support (p=0.354), which works reciprocally between the two. In terms of demographic information, such as students’ current age, age at their first menarche, information about puberty, and parents’ educational attainment, shows a slight influence on students’ knowledge. Interestingly, mothers’ education level significantly correlates with school support, while information from friends has a negative statistical correlation with school support. Yet most demographics show no statistically significant correlation with both students’ knowledge and school support. This finding implies the call for boarding schools to support their young female students while they are transitioning through puberty with confidence in relation to their ample knowledge.